Feasibility, Tolerability and Efficacy of Carfilzomib in Combination with Lenalidomide and Dexamethasone in Relapsed Refractory Myeloma Patients: A Retrospective Real-Life Survey of the Sicilian Myeloma Network - Concetta Conticello (Journal of Clinical Medicine, 2019)
Background: The ASPIRE (NCT01080391) phase 3 trial showed the efficacy of carfilzomib, lenalidomide and dexamethasone (KRd) triplet for relapse and refractory multiple myeloma (RRMM). However, little is known about safety and efficacy of KRd outside a clinical trial context. Methods: Herein we report real life results of KRd given to 130 RRMM patients from 12 Sicilian Centers. Results: Median age was 62 years; patients had received a median of two previous lines of treatment (range 1−10) and 52% were refractory to previous treatment. Median number of KRd cycles was 12 (2−29), with a mean duration of treatment of 12 months; 21 patients had received at least 18 cycles. Overall response rate was 61%, including 18% complete response. Median PFS was 22.9 months, median OS was not reached. Creatinine clearance >30 mL/min, quality of the best achieved response and standard Fluorescence In Situ Hybridization (FISH) risk were independent predictors of favorable outcome. Patients who received the full-dosage of carfilzomib in the first two cycles had a better outcome. Conclusions: KRd was effective and well tolerated and in a considerable proportion of patients, therapy continued beyond the 18th cycle. The finding of a better outcome in patients with the higher cumulative dose of carfilzomib in the first two cycle encourages to maintain the maximum tolerated dose.